2023
DOI: 10.1126/sciimmunol.adg0878
|View full text |Cite
|
Sign up to set email alerts
|

Sustained CD28 costimulation is required for self-renewal and differentiation of TCF-1 + PD-1 + CD8 T cells

Etienne Humblin,
Isabel Korpas,
Jiahua Lu
et al.

Abstract: During persistent antigen stimulation, such as in chronic infections and cancer, CD8 T cells differentiate into a hypofunctional programmed death protein 1–positive (PD-1 + ) exhausted state. Exhausted CD8 T cell responses are maintained by precursors (Tpex) that express the transcription factor T cell factor 1 (TCF-1) and high levels of the costimulatory molecule CD28. Here, we demonstrate that sustained CD28 costimulation is required for maintenance of antiviral T cells during chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…It is well established that mitochondrial dynamics are critical for oxidative metabolism. 73 , 74 , 111 , 112 Our data show that Sel1L loss alters mitochondrial morphology, leading to an increase in smaller (i.e., more fissed) mitochondria and increased MERCS formation. Multiple lines of evidence link chronic ER stress to mitochondrial fission and increased mitochondrial-ER contacts.…”
Section: Discussionmentioning
confidence: 63%
“…It is well established that mitochondrial dynamics are critical for oxidative metabolism. 73 , 74 , 111 , 112 Our data show that Sel1L loss alters mitochondrial morphology, leading to an increase in smaller (i.e., more fissed) mitochondria and increased MERCS formation. Multiple lines of evidence link chronic ER stress to mitochondrial fission and increased mitochondrial-ER contacts.…”
Section: Discussionmentioning
confidence: 63%
“…Training on DCs impacted the functional shape of CD8 T cells infiltrating melanoma tumors, which displayed the expression of Ki67 and Granzyme B, associated with a higher expression of CD44, suggesting that these cells acquired a memory phenotype. Recent reports have suggested that the CD28/CD86 axis in a tumor context is necessary to prevent final CD8 T cell exhaustion and its accumulation ( 79 ).. Moreover, this axis rewires the exhaustion trajectory in CD8 T cells, leading to a more central memory phenotype rather than an exhausted phenotype ( 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the decline in the number of CD8 + T cells in the LI of middle-aged UREΔ/Δ mice was not as significant as was observed for CD4 + T cells. Whether this occurred because they are stem-like CD8 T cells that are maintained because of persistent antigen exposure ( Lin et al, 2016 ; Gill et al, 2023 ; Humblin et al, 2023 ), which would be encountered in the large bowel, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%